The impact of international trade on economic growth in Malaysia / Nur Irdina Haryani Husin - Husin, Nur Irdina Haryani (Faculty of Business and Management, 2018)
This paper aims to conduct a comparative study which also to examine whether Malaysia’s economic growth affected by the international trade. Economic growth of Malaysia declined in the year of 1980s and was continually decreased. Therefore, this paper has empirically examined the impact of international trade on economic growth in Malaysia. This study also use gross domestic product as proxies for economic growth, the ordinary least square technique was employed to estimate the impact international trade on gross domestic product. The objectives of this study is to investigate the significant relationship between the indicators of international trade and economic growth based on time series data. This study also run diagnostic checking to test for the normality, multicollinearitty, autocorrelation and heteroscedasticity problem. Thus, the results showed there is no normality, multicollinearitty, autocorrelation and heteroscedasticity problem. The results of the analysis shows that all the variables except for export and inflation were statistically significant. For the ADF, PP and KPSS unit root test, all variables showed stationary at the first difference.